PENGENDALIAN PENYAKIT LAYU FUSARIUM PISANG (Fusarium oxysporum f.sp.cubense) DENGAN SOLARISASI TANAH DAN BAKTERI ANTAGONIS - Andree Saylendra (Jurnal Agroekoteknologi, 2009)
ABSTRACTThe objective of the research is to investigate the effectiveness of soil solarization and antagonist bacteria in controlling fusarial wilt of banana.The experiment was conducted in farmer field by randomized complete block of two factors.  The treatment in the field, factor A is solarization (without solarization, three weeks of solarization, and four weeks of solarization); factor B is antagonist bacteria (without bacteria, bacteria 1, and bacteria 2). The treatment is replicated three times.  The number of banana’s plant for each treatments are 4-6 plants. The result of field research showed that single treatment of solarization, bacteria even combination between them did not significantly affect to suppress the incident of Foc.Keywords:  Fusarium oxysporum f.sp.cubense, soil solarization, antagonist bacteria